ARTIFICIAL INTELLIGENCE IN ENVIRONMENTAL SCIENCE AND ENGINEERING: A REVIEW OF APPLICATIONS, CHALLENGES, AND SUSTAINABLE FUTURES - Ahmad Ibrahim Maqbool,; Zaib-un-Nisa,; Shahzaib Kiayani,; Amna Safdar, (Spectrum of Engineering Sciences, 2025)
In environmental engineering and science, artificial intelligence (AI) is becoming an essential tool which deals with serious global issues such as pollution, biodiversity loss, climate change and helping victims of disasters. The broad range of AI applications emphasized in this review article includes waste management, disaster anticipation, air and water quality assessment, climate modelling process and monitoring of the environment. AI technologies such as neural networks and deep learning have significantly improved the processing of data, real time forecasting and decision making process. These advancements promote resource efficiency, enable early warning systems to be accessible and increase the success rate of environmental solutions. Public health and the safeguarding of ecosystems that are natural both benefit from the massive, precise information gathering and analysis made available by the integration of the AI into environmental tracking mechanisms. For effective accountable AI execution, data restrictions, model transparency, excessive use of energy and ethical issues have to be overcome. The role of AI in achieving sustainable development goals (SDGs) and affecting future environmental laws are both addressed. This paper also highlights that AI has the potential to completely change environmental investigation and engineering through looking at current advances, limitations and potential future developments and it also promotes ethical development and multidisciplinary collaboration in order to achieve for a long time sustainable development.